REARING OF "AYU' LARVAE (PLECOGLOSSUS ALTIVELIS) BY ARTIFICIAL DIETS. II. EFFECTS OF TAURINE, URSO-20, GLUTATHIONE AND TACHINASE SUPPLEMENTS ON GROWTH AND SURVIVAL - Sultana, N; Hossain, M A; Furuichi, M; Yone, Y (Indian Journal of Fisheries, 2011)
Larvae of freshwater sweet fish 'Ayu' (Plecoglossus altivelis) were raised on micro - capsulated artificialdiet suplemented with taurine, ursodesoxychloric acid (urso-20), glutathione and tachinase. The growthand survival of larvae raised with micro - capsulated diets were compared with those reared on liveplanktonic feed. Supplements of taurine, Urso-20 and glutathione in microcapsulated diet apparentlyretard the growth and survival rate of larvae. On the other hand, supplements of tachinase showed relativelybetter growth and survival rate compared to one without it. However, the larvae raised on liveplanktonic feed (rotifer) yielded much better growth and survival compared to those raised on micro -capsulated artificial diet.